The Effect of Profitability on Stock Prices of LQ45 Firms - Mirna Triana; Christine Debbie (CAKRAWALA : Management Science Journal, 2025)
This study aims to examine the impact of profitability, measured by Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM), on stock prices of companies listed in the LQ45 index of the Indonesia Stock Exchange between 2021 and 2023. The results show that only NPM significantly affects stock prices, while ROA and ROE do not have a significant individual effect. The F-test indicates that all three profitability ratios together have a significant effect on stock prices, suggesting that although individual ratios may not sufficiently explain stock price movements, their combined effect provides a more complete picture of a company’s financial health. The Fixed Effect Model (FEM) used in this study effectively controls for unobserved heterogeneity among companies. The adjusted R² value of 47.1% suggests that while profitability plays an important role in explaining stock price variation, other factors such as market sentiment, macroeconomic conditions, and external variables also influence stock prices. The findings highlight that investors tend to assess profitability through a composite approach, considering multiple financial ratios together rather than relying on a single metric. This study provides valuable insights into how investors react to financial signals in emerging market contexts and emphasizes the importance of external factors in shaping investment decisions